Konsep Kebebasan dalam Novel Pasung Jiwa Karya Okky Madasari : Analisis Filsafat Eksistensialisme Soren Kierkegaard - Ardiansyah, Bagus; Maraimbang, Maraimbang; Utomo, Wahyu Wiji (Lembaga Yasin AlSys, 2023)
Literature and philosophy are like two sides of a coin that cannot be separated from each other. There is even a reciprocal relationship between literature and philosophy. It can be proven that the birth of a literary work is the author's philosophical reflection on the reality he faces. raises various problems related to mental health and the stigma that still exists in society and the research problem that will be identified in this thesis is the concept of freedom in the novel